The Impact of Syrians Refugees on the Turkish Labor Market - Del Carpio, Ximena V.; Wagner, Mathis (World Bank, Washington, DC, 2015)
Civil war in Syria has resulted in more than four million refugees fleeing the country, of which 1.8 million have found refuge in Turkey, making it the largest refugee-hosting country worldwide. This paper combines newly available data on the 2014 distribution of Syrian refugees across subregions of Turkey with the Turkish Labour Force Survey, to assess the impact on Turkish labor market conditions. Using a novel instrument, the analysis finds that the refugees, who overwhelmingly do not have work permits, result in the large-scale displacement of informal, low-educated, female Turkish workers, especially in agriculture. While there is net displacement, the inflow of refugees also creates higher-wage formal jobs, allowing for occupational upgrading of Turkish workers. Average Turkish wages have increased primarily as the composition of the employed has changed because of the inflow of refugees.